Bodily Abjection and the Politics of Resistance in Tom Paulin's Greek Tragedies. (21st December 2020) - Torrance, Isabelle
Abstract: Tom Paulin's Greek tragedies present extremes of bodily abjection in order to service of a politics of resistance that is tied, in each case, to the political context of the drama's production. The Riot Act (1984), Seize the Fire (1989), and Medea (2010), share a focus on the degradation of oppressed political groups and feature characters who destabilize the status quo. Yet the impact of disruptive political actions is not ultimately made clear. We are left wondering at the conclusion of each tragedy if the momentous acts of defiance we have witnessed have any power to create systemic change within politically rigged systems. The two 1980s plays are discussed together and form a sequence, with The Riot Act overtly addressing the Northern Irish conflict and Seize the Fire encompassing a broader sweep of oppressive regimes. The politics of discrimination in Medea are illuminated by comparison with similar themes in Paulin's Love's Bonfire (2010). Unlike other Northern Irish adaptations of Greek tragedy, Paulin's dramas, arrested in their political moments, present little hope for the immediate future. Yet in asking us to consider if individual sacrifice is enough to achieve radical change they maintain an open channel for political discourse.